2020
DOI: 10.1002/jwmg.21967
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Coyote Densities with Local, Discrete Bayesian Capture‐Recapture Models

Abstract: Recent advances in noninvasive genetic sampling and spatial capture-recapture (SCR) techniques are particularly useful for monitoring cryptic wildlife species such as carnivores. In southern Arizona, USA, coyotes (Canis latrans) are thought to negatively affect endangered Sonoran pronghorn (Antilocapra americana sonoriensis), although no estimates of coyote abundance or monitoring programs exist. Sonoran pronghorn are provided supplemental feed and water in this region, resulting in areas where pronghorn and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 105 publications
0
8
1
Order By: Relevance
“…22.2 in Bekoff & Gese, 2003; abstract summaries in Mastro et al, 2012), those in the NC Recovery Area were lower than densities reported in all regions except those reported at the coyote's northernmost range limits (e.g., O'Donoghue et al, 1997). We also report lower coyote density estimates than those reported in more recent studies such as those conducted in southwest Arizona (53.0–112 coyotes/1000 km 2 ; Woodruff et al, 2021), the Great Basin Desert of Utah (70–80 coyotes/1000 km 2 ; Lonsinger et al, 2018), the Appalachian region of Virginia (24–90 coyotes/1000 km 2 ; Morin et al, 2016), and the Savannah River region of South Carolina (800–1500 coyotes/1000 km 2 ; Kilgo et al, 2017). Of those studies, Appalachia and the Savannah River region were neighboring areas of the NC Recovery Area exhibiting greater densities of coyotes.…”
Section: Discussioncontrasting
confidence: 67%
“…22.2 in Bekoff & Gese, 2003; abstract summaries in Mastro et al, 2012), those in the NC Recovery Area were lower than densities reported in all regions except those reported at the coyote's northernmost range limits (e.g., O'Donoghue et al, 1997). We also report lower coyote density estimates than those reported in more recent studies such as those conducted in southwest Arizona (53.0–112 coyotes/1000 km 2 ; Woodruff et al, 2021), the Great Basin Desert of Utah (70–80 coyotes/1000 km 2 ; Lonsinger et al, 2018), the Appalachian region of Virginia (24–90 coyotes/1000 km 2 ; Morin et al, 2016), and the Savannah River region of South Carolina (800–1500 coyotes/1000 km 2 ; Kilgo et al, 2017). Of those studies, Appalachia and the Savannah River region were neighboring areas of the NC Recovery Area exhibiting greater densities of coyotes.…”
Section: Discussioncontrasting
confidence: 67%
“…Assuming that the total suitable habitat in the sampled region is 800 km 2 , that is, the total area sampled not including the mountainous habitat in the southeast, the density of coyotes in the area is 0.10 individuals/km 2 (95% CI = 48–210 or 0.06–0.26 coyotes/km 2 ). Previous studies of western coyotes have reported values including 0.053–0.112 coyote/km 2 (Woodruff et al, 2021), 0.14 coyotes/km 2 (Ralls & White, 1995), and 0.07–0.08 coyotes/km 2 (Lonsinger, Lukacs, et al, 2018). In general, coyote densities tend to be lower in desert areas where they are sympatric with kit foxes because coyotes have higher water needs than kit foxes which are better adapted to arid environments (Lonsinger, Lukacs, et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Because canids tend to be elusive and difficult to study, noninvasive genetic sampling methods have been utilized extensively, for example, to estimate abundance and genetic diversity of coyotes (e.g., Morin et al, 2016; Prugh et al, 2005; Woodruff et al, 2021) and kit foxes (e.g., Lonsinger et al, 2018; Lonsinger et al, 2018; Wilbert et al, 2015, 2019). Scat, the most commonly collected material in noninvasive genetic studies (Waits & Paetkau, 2005), is particularly easy to identify in the field because canids defecate to mark territories (Morin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the red fox ( Vulpes vulpes ) has adapted to cities globally, with densities up to four times greater in cities than in adjacent rural areas (Marks & Bloomfield, 1999 ), and human footprint is the biggest driver of fox home range size on a global scale (Main et al., 2020 ). Coyote ( Canis latrans ) populations are denser around clumped natural resources (Woodruff et al., 2021 ), and have also adapted to urban environments, where they can reach higher densities than in rural areas (Fedriani et al., 2001 ; Jonathan, 2011 ). Coyote home ranges are also smaller in urban environments (Grubbs & Krausman, 2009 ), indicating that they are obtaining sufficient resources from a smaller area than they would normally obtain from more natural settings.…”
Section: Introductionmentioning
confidence: 99%